2020
DOI: 10.1093/brain/awaa275
|View full text |Cite
|
Sign up to set email alerts
|

Brain TSPO-PET predicts later disease progression independent of relapses in multiple sclerosis

Abstract: Overactivation of microglia is associated with most neurodegenerative diseases. In this study we examined whether PET-measurable innate immune cell activation predicts multiple sclerosis disease progression. Activation of microglia/macrophages was measured using the 18-kDa translocator protein (TSPO)-binding radioligand 11C-PK11195 and PET imaging in 69 patients with multiple sclerosis and 18 age- and sex-matched healthy controls. Radioligand binding was evaluated as the distribution volume ratio from dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 60 publications
10
96
0
1
Order By: Relevance
“…Indeed, it was shown that in the brain of advanced SPMS patients, 57% of the plaques were of the chronic active type, with increased TSPO binding [ 60 ]. Moreover, an in vivo TSPO/PET study demonstrated that increased TSPO radioligand uptake in NAWM predicts later disability progression independent of relapse activity [ 61 ]. TSPO detects microglia activation but does not allow for the investigation of the different phenotypes.…”
Section: Mechanism Of Disease Progression In Msmentioning
confidence: 99%
“…Indeed, it was shown that in the brain of advanced SPMS patients, 57% of the plaques were of the chronic active type, with increased TSPO binding [ 60 ]. Moreover, an in vivo TSPO/PET study demonstrated that increased TSPO radioligand uptake in NAWM predicts later disability progression independent of relapse activity [ 61 ]. TSPO detects microglia activation but does not allow for the investigation of the different phenotypes.…”
Section: Mechanism Of Disease Progression In Msmentioning
confidence: 99%
“…To date, TSPO-binding [ 11 C]PK11195 ligand has been widely used in MS. [ 11 C]PK11195 PET studies have shown an increased tracer distribution in the NAWM, T2-, T1- and Gadolinium-enhanced cortical and subcortical GM in MS patients compared with healthy controls [ 121 , 122 , 123 , 124 , 125 , 126 ]. Interestingly, at the very early stages of the disease, patients already display an increased extent of microglia activation throughout NAWM, which predicts disease course over the follow-up [ 127 , 128 ]. Additionally, it has been demonstrated that increased neuroinflammation in the thalamus is linked with cortical atrophy [ 129 ].…”
Section: Functional and Metabolic Correlatesmentioning
confidence: 99%
“…The discovery of easily accessible biomarkers of microglial phenotypes may also eventually allow real-time monitoring of treatment effects in the living human brain using techniques such as PET. 62 Already in liver cirrhosis, the safety and tolerability of autologous macrophage infusion following their in vitro polarization to an advantageous pro-regenerative phenotype have been demonstrated in a phase I clinical trial. 127 This provides an exciting proof of concept for the feasibility of therapeutic neuroprotective microglial replacement in MS patients.…”
Section: Human Stem Cell-derived Preclinical Models To Study Microglimentioning
confidence: 99%